Examining housing selection problematics in Jakarta's transit-oriented development (TOD) areas Case study: MRT Jakarta tod area - Gunawan Gunawan; Arief Bimantoro Suharko (Sean Institute, 2024)
This research aims to explore the issues surrounding residential choices in Transit Oriented Development (TOD) areas and to identify factors influencing the decision to reside in such areas. A case study approach was employed, utilizing data collection techniques such as interviews and observations, with data analysis conducted through pattern matching. The study findings indicate that the majority of residents in TOD areas are productive individuals, originating from outside Jakarta. Key factors influencing residential choices include accessibility to public transportation, particularly the Jakarta MRT, and proximity to workplaces. Residential choice issues encompass various housing options, destination accessibility, integration of public transportation, transportation costs, and housing prices. Government support in facilitating vertical development permits and endorsing Public-Private Partnerships (PPPs) is essential to enhance the population density in TOD areas.